Development Analysis of Good Corporate Governance in Its Role on Financial Distress: Systematic Literature Review - Damayani, Fitri; Fuadah, Luk Luk; Yuniarti, Emylia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This study aims to determine the development, role, and gaps in research literature related to the relationship between GCG and financial distress. The method used is Systematic Literature Review (SLR) using articles from Science Direct, Emerald, Proquest, Taylor & Francis, and DOAJ. There are 35 articles classified based on publication year, country of study, company sector, theory, dependent and independent variables. The articles are divided into three timelines: before pandemic, during pandemic, and after pandemic. The results of this study show that there is development in terms of the company sector, GCG variables used, and measurement of financial distress. The summary of the influence of GCG provides insight that these variables can play a role in overcoming financial distress through audit committee, number of board members, independence of directors and commissioners, audit committee competence, gender diversity, and ownership. The results also found a significant research gap in terms of research type, research country, company sector, GCG variables, and financial distress measurement. This research is expected to provide information for companies to pay attention to the currently developing GCG variables and provide information for further researchers to develop the topic to obtain more comprehensive results.